"Well, He Is Paid to Be Violent…": How Athlete Identity Alters Perceptions of Domestic Violence Incidents. Issue 5 (20th October 2022) - Brown, Kenon A.; Billings, Andrew C.; Lewis, Melvin; Moscowitz, Leigh
Abstract: The purpose of this study is to determine if perceptions of violence related to race, gender and sport will impact audience reactions to domestic violence issues involving an athlete. Specifically, this study will examine how these elements of an athlete's identity could affect his/her perceived image when faced with domestic violence accusations. A 3 (perceived race) X 2 (gender) X 2 (sport) factorial experiment was conducted using a national convenience sample of 626 participants from Qualtrics Panels. Results provided evidence that an athlete's race and gender could have an impact on their perception during domestic violence cases, with the male athlete (regardless of the race of the athlete) and the White athlete (regardless of the gender of the athlete) facing more negative perceptions. Furthermore, the violent nature of the sport did not have an impact on the perceptions of the athlete. This study provides further evidence about the role that gender and race play in how domestic violence is perceived during criminal transgressions.